Gender, media, and organization : challenging mis(s)representations of women leaders and managers - Elliott, Carole, 1966-; Stead, Valerie, 1958-; Mavin, Sharon; Williams, Jannine (Women and leadership (Charlotte, N.C.), 2016)
Gender, Media, and Organization: Challenging Mis(s)Representations of Women Leaders and Managers is the fourth volume in the Women and Leadership: Research, Theory, and Practice series. This cross disciplinary series from the International Leadership Association draws from current research findings, development practices, pedagogy, and lived experience to deliver provocative thinking that enhances leadership knowledge and improves leadership development of women around the world. This volume addresses the lack of critical attention in leadership research to how women leaders and professionals are represented in the media. The volume acts as a companion piece to a Seminar Series, funded by the UK's Economic and Social Sciences Research Council (ESRC), to address this gap in the research. The lack of research interrogation of gendered media representations of women leaders and professionals is a surprising omission given the wealth of evidence from stakeholders outside academia revealing that women, and women leaders, continue to be underrepresented across all forms of media outlet. This volume contributes to social change, equality, and economic performance by raising consciousness about women's lack of representation in the media and challenges gendered mis(s)representations of women professionals and leaders in the media through the presentation of a range of empirical investigations and methodological approaches. The volume contributors use various theories and conceptualizations to problematize and analyze women's limited representation in the media, and the gendered representations of women professionals and leaders. Together, the volume's 14 chapters reflect the beginning of a rich, diverse, emergent strand of academic research that interrogates relationships between the media in its multiple forms and women's leadership. Illuminating the positioning of women leaders and professionals as both complex and problematic, these chapters offer an important agenda for management and organization scholars. They attest to the need to describe and make visible women's mis(s)representations in the media while drawing attention to the importance of situating these mis(s) representations in the broader social, economic, historical, cultural, and political context as a means to gain insight into their development and evolution. As a rich and diverse site of research, examination of the media calls for a broad methodological repertoire. The chapters in this book draw from multiple sources and include, among others, the development of thematic analysis to illuminate stereotypes, the use of critical discourse analysis to understand professional women's experience, a rhetorical analysis of the covers of Time magazine, and an interrogation of the power dynamics manifested in the media's practice of nicknaming women leaders. Gender, Media, and Organization is a first step in stimulating further research that poses critical questions concerning gendered and sexualized representations of women leaders in textual and visual forms, and considers the media's influence on gender equality and social justice. The chapters offer fruitful avenues for future research to continue the momentum of challenging gendered media representations of women leaders and professionals.